Legal Recognition of Digital Identity in Cross-Border Electronic Transactions: Reconstructing Normative Frameworks for Legal Certainty - Andi Hartawati; Toman Sony Tambunan; Elva Mahmudi (Lex Recta: Journal of Law and Normative Justice, 2026)
This study examines the legal recognition of digital identity in cross-border electronic transactions and evaluates its significance for the establishment of legal certainty within contemporary digital commerce. The rapid expansion of transnational electronic trade has exposed structural weaknesses in existing legal frameworks, particularly regarding the attribution, authentication, and recognition of digital identities across different jurisdictions. Employing a normative, doctrinal, and comparative legal approach, the research analyzes international legal instruments, Indonesian legislation, regulatory frameworks on electronic signatures and trust services, and comparative models of digital identity governance. The analysis demonstrates that current regulations primarily emphasize technological authentication and transactional validity while providing insufficient mechanisms for mutual legal recognition of digital identities across borders. Jurisdictional fragmentation, regulatory divergence, and inconsistencies in evidentiary recognition generate uncertainty concerning contractual enforceability, accountability, consumer protection, and cross-border regulatory enforcement. The study proposes a reconstructed normative framework founded upon mutual recognition, regulatory equivalence, legal attribution, data protection integration, and procedural enforceability. This framework reconceptualizes digital identity as a transnational legal institution capable of supporting interoperability, accountability, and legal certainty within the evolving architecture of global electronic commerce.